Trigger factor reduces the force exerted on the nascent chain by a cotranslationally folding protein - Nilsson, Ola B.; Müller-Lucks, Annika; Kramer, Günter; Bukau, Bernd; von Heijne, Gunnar (Journal of molecular biology, 2016)
Cotranslational protein folding can generate pulling forces on the nascent chain that can affect the instantaneous translation rate and thereby possibly feed back on the folding process. Such feedback would represent a new way of coupling translation and folding, different from coupling based on, for example, codon usage. However, to date, we have carried out the experiments used to measure pulling forces generated by cotranslational protein folding either in reconstituted in vitro translation systems lacking chaperones, in ill-defined cell lysates, or in vivo; hence, the effects of chaperones on force generation by folding are unknown. Here, we have studied the cotranslational folding of dihydrofolate reductase (DHFR) in the absence and in the presence of the chaperones trigger factor (TF) and GroEL/ES. DHFR was tethered to the ribosome via a C-terminal linker of varying length, ending with the SecM translational arrest peptide that serves as an intrinsic force sensor reporting on the force generated on the nascent chain when DHFR folds. We find that DHFR folds into its native structure only when it has emerged fully outside the ribosome and that TF and GroEL alone substantially reduces the force generated on the nascent chain by the folding of DHFR, while GroEL/ES has no effect. TF therefore weakens the possible coupling between cotranslational folding and translation.